PENGARUH DRY NEEDLING TERHADAP PENURUNAN NYERI PADA PASIEN KASUS SPASME UPPER TRAPEZIUS DI RW 1 DESA GURAH KECAMATAN GURAH KABUPATEN KEDIRI - Rizky Pratama Putra; Agung Hadi Endaryanto; Sartoyo Sartoyo; Nurul Halimah (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Background: Spasm is an informal, non-specific term often used to describe musculoskeletal pain. Pain is an uncomfortable and unpleasant feeling associated with tissue damage. Pain is also a subjective feeling that is felt. Spasm pain that often occurs is pain in the upper trapezius muscle area which is caused by work, stress and posture. Dry needling is a method that uses dry and sterile needles which is often used to help reduce pain in muscle trigger points. The aim of this study was to determine the effect of dry needling on reducing pain in patients with cases of upper trapezius spasm. Methods: The research design used was quasi experimental with a pre and post-test one group design research type with a total of 17 respondents who met the exclusion and inclusion criteria using a purposive sampling technique. Pain was measured using a visual analog scale (VAS) which was carried out before and after physiotherapy treatment in 1 group, namely; dry needling with 1 administration. Statistical tests use the Wilcoxon test. Results: When giving dry needling, the median value was pre 6 to post 2 with a P value = 0.00. Conclusion: it can be concluded that dry needling is effective in reducing upper trapezius spasm pain. Keywords: Dry Needling, Pain, Spasm